2020
DOI: 10.1002/mrd.23397
|View full text |Cite
|
Sign up to set email alerts
|

l‐Arginine supplementation of gilts during early gestation modulates energy sensitive pathways in pig conceptuses

Abstract: Dietary l‐arginine (ARG) supplementation has been studied as a nutritional strategy to improve reproductive performance of pregnant sows, since arginine is a conditionally essential amino acid. However, reports addressing the molecular mechanisms that mediate supplementation effects on embryos and fetuses development are still scarce. Therefore, we aimed to evaluate the effects of 1.0% ARG supplementation of commercial pregnant gilts on genes and proteins from energy metabolism and antioxidant defense pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…At day 35 however, embryos from dams supplemented with arginine were smaller. In a different paper by the same authors [66], arginine differentially regulated expression of embryonic genes involved in energy metabolism and in the mTOR pathways at day 25 of gestation, whereas at day 35, these effects were not observed. Collectively, these new findings point to the effects of arginine fed to the dam on embryo development and gene expression in addition to the effects described in earlier work on placental capacity.…”
Section: Effects Of Nutrition From Implantation Onwardsmentioning
confidence: 88%
“…At day 35 however, embryos from dams supplemented with arginine were smaller. In a different paper by the same authors [66], arginine differentially regulated expression of embryonic genes involved in energy metabolism and in the mTOR pathways at day 25 of gestation, whereas at day 35, these effects were not observed. Collectively, these new findings point to the effects of arginine fed to the dam on embryo development and gene expression in addition to the effects described in earlier work on placental capacity.…”
Section: Effects Of Nutrition From Implantation Onwardsmentioning
confidence: 88%
“…We analyzed the pathways of different metabolites and found that the metabolites mainly belonged to protein digestion and absorption; glyoxylic acid and dicarboxylic acid metabolism; alanine, glutamic acid and proline metabolism; and glucose metabolism. These metabolic pathway disorders may be involved in the occurrence and development of fetal growth restriction [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study is part of a whole experiment initially designed to understand the effects of maternal dietary L-arginine supplementation on pig embryos at 25 days old and fetuses at 35 days old [ 12 , 13 ], as well as compare organogenesis. Particularly, in the current study, we describe the transcriptional changes that occur during the development stages instead of the effects of L-arginine supplementation.…”
Section: Methodsmentioning
confidence: 99%